Karakteristik Fermentasi Kedelai yang Diperkaya Mineral Zn dengan Rhizopus sp.: Fermentation Characteristics of Soybean Enriched with Zn Minerals Using Rhizopus sp - Febriyanti Regina Cahyani; Toto Toharmat; Iwan Prihantoro (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Zinc (Zn) supplementation is needed by livestock to overcome decreased body immunity due to problems with feed quality and environmental stress that affect their productivity levels. This research aims to analyze the fermentation characteristics of Rhizopus sp. on soybeans as a substrate with different levels of Zn mineral and fermentation times. This study uses a complete factorial design with 4 replications. Factor 1 is the Zn mineral level, namely 0, 400, 800, 1200, and 1600 ppm. Factor 2 is the fermentation time, namely 0, 1, 2, 3, and 4 days. The data were analyzed using Analysis of Variance (ANOVA), and significantly different treatments were further tested with Duncan's Multiple Range Test (DMRT) in the SPSS 25 program. The results of the analysis indicate that Zn levels ≥800 ppm significantly (p<0.05) inhibit mycelium development on the first day of fermentation. Increasing Zn levels significantly (p<0.05) decreases the average acidity level and significantly (p<0.05) increases the substrate ash content, while fermentation time significantly (p<0.05) increases acidity level and decreases biomass, dry matter content, organic matter, and ash content of substrate. Zn level and fermentation time treatments influence the growth and performance of Rhizopus sp. in transforming soybean nutrients. Key words: fermentation, Rhizopus sp., soybean, Zn mineral